Cucurbitacin E, An Experimental Lead Triterpenoid with Anticancer, Immunomodulatory and Novel Effects Against Degenerative Diseases. A Mini-Review - Attard, Everaldo; Martinoli, Maria-Grazia (Current Topics in Medicinal Chemistry, 2015)
A growing number of studies have revealed that natural molecules own interesting antioxidant and anti-apoptotic properties in cell culture as well as in animal models of human diseases such as cancer, inflammatory and neurodegenerative diseases. During the past sixty years, several cucurbitacins have been isolated from a number of cucurbitaceous species, amongst others. Cucurbitacins are triterpenoid compounds originally identify as the bitter components of the Cucurbit family that demonstrated several pro-survival activities in various model of cellular decay. Specifically, Cucurbitacin E (CuE), an oxygenated tetracyclic triterpenoid, has been investigated in a wider array of bioactivities, mainly immunomodulatory. Recently, CuE has been reported to possess anti-inflammatory and anti-tumorigenic properties mediated by its action on the cellular cytoskeleton, on mitotic pathways as well as on cellular autophagy. Few studies also pinpoint the role of CuE in the nervous system as cytostatic for gliomas and neuroprotective in a model of Parkinson’s diseases. This review deals with the use of CuE in various experimental models as one of the most promising therapeutic natural molecules against cancer proliferation, as an immunomudulator and for the prevention of neurodegeneration.
Keywords: anti-oxidant